Data path allocation with interconnection optimization in high-level synthesis - Zhu, Hongwei. (2008)
In this thesis, a layout area estimation model based on bit-sliced standard cell design style was established. In this model, the unit area is formulated as a function of the 2-input NAND gate equivalent, and the routing track requirement is estimated using a probabilistics model.